Indoor air pollutant exposure and eosinophil cationic protein as an upper airway inflammatory biomarker among preschool children - Andrew, Dana Wesley; Jalaludin, Juliana (Elsevier, 2015)
The upper and lower airways of the respiratory tract are functionally linked, with inflammation in the former playing a vital role in the pathogenesis of asthma and allergy. Studying the association between indoor air pollutants with upper airway inflammation in children will help improve childhood asthma and allergy management related to poor indoor air quality. A cross-sectional study was conducted among preschool children in industrial (Kelana Jaya and Shah Alam) and suburban (Semenyih and Hulu Langat) areas in Selangor, Malaysia. A questionnaire adapted from the American Thoracic Society and International Study on Asthma and Allergy in Children was distributed to obtain the respondents’ background information, school, and home environment. Eosinophil cationic protein (ECP) concentrations in nasal swab samples were collected and analyzed to determine the prevalence of upper airway inflammation. An indoor air quality (IAQ) assessment was also conducted in seven preschools in both industrial and suburban areas, including parameters such as particulate matter up to 10 μm in size (PM10), volatile organic compounds (VOCs), total mold, total bacteria, relative humidity, and air temperature. Statistical analysis shows significant differences in PM10, total mold, total bacteria and relative humidity between the study areas (p < 0.05). The ECP levels among respondents vary significantly between study areas (t = 8.473, p < 0.001). The VOC concentration and ECP level are significantly correlated(prevalence ratio 6.41; 95% CI, 1.268 to 32.394) after controlling all confounders. This study concludes that exposure to indoor air pollutants increases the risk of respiratory problems and may have an impact on the inflammatory and secretory response of the nasal mucosa